Problem of the Decohesive Carrying Capacity of a Cylindrical Shell Under a Ring of Forces and Tension - Bihn, Tran-Le; Życzkowski, M. (Engineering Transactions, 1984)
Termination of the process of elastic-plastic deformations of a sandwich cylindrical shell under a simultaneous ring of radial forces and axial tension is studied in detail. The materiał is assumed to be perfectly elastic-plastic, incompressible and subject to the Huber-Mises-Hencky yield condition. The decohesive carrying capacity is in this case determined by an infinite increase of axial strains ex in the outer layer at the point x=O. The relevant singularity is described by generalized power series and, using those series combined with numerical integration, a concave interaction curve corresponding to the decohesive carrying capacity is determined.